Sentinel lymph node surgery in prostate cancer using magnetic particles. Issue 2 (March 2018) - Winter, Alexander; Engels, Svenja; Wawroschek, Friedhelm
Abstract : Purpose of review: Superparamagnetic iron oxide nanoparticles (SPIONs) are tested to identify sentinel lymph nodes (SLNs) to exploit the advantages of targeted pelvic SLN dissection (sPLND), while circumventing the disadvantages of established radioactive labeling. Here we review recent studies about sPLND in prostate cancer (PCa), including the first results of SLN detection using intraprostatic SPION-injection. Recent findings: A recent systematic literature review reveals that the diagnostic accuracy of sPLND is comparable with extended PLND (ePLND). sPLND combined with ePLND achieve better node removal by increasing the number of affected nodes. The first sentinel-based nomogram predicting lymph node invasion is established. A sentinel-nomogram update provides comparative predictions relative to ePLND models. sPLND using a magnetometer and SPIONs as a tracer is successful whenever applied to PCa, and SLN identification using MRI after intraprostatic injection of SPIONs is feasible. SLNs are present in an unexpectedly high number outside the ePLND template. Summary: SLN detection outside the ePLND template and the increased diagnostic value of sPLND compared with ePLND supports the individualized extension of PLND using sPLND in PCa. SPION-MRI, combined with a hand-held magnetometer, provides a nonradioactive technique for preoperative and intraoperative SLN localization. Further studies are required to evaluate the effects of sPLND on oncological outcomes.